Protective Functions of Forests - (Paper Contributed to the United Nations Scientific Conference on Resources, 1949) - Ranganathan, C. R. (Indian Forester, 1950)
The protective influence of forests on the habitat has been noted and recorded from the earliest times. During the past 100 years this has been the subject of observation and study. Naturalists are con-vinced of the beneficial effects of forests on the meteorological and hydrological conditions and of the large part that properly distributed and well maintained forests play in the well-being of rural and agricultural communities. Careful experimental studies have indicated that the influence of forests on major climatic factors (especially rainfall) and on stream flow may have been overstated; but generally speaking, the influence of forests is to mitigate and ameliorate excesses in the factors of the locality. Historical evidence from many countries proves conclusively that the soil and physical conditions deteriorate with the destruction of forests or their degradation through excessive grazing or burning. Forest devastation may in time lead to the destruction of the physical bases of life, the spread of desert conditions, and the extinction of the local civilization. Comparison of the protective efficiency of grassland, cropland and forest leads to the conclusion that the reactions of the forest on the climate and water regime of the locality are most constant and sustained. By forest is meant a community of trees possessing a more or less continuous canopy with or without subordinate shrubby or herbaceous vegetation. Such a forest renders the air inside it cool and damp, protects the soil from direct exposure to the sun, retards the flow of air currents and promotes the accumulation of an absorptive and protective layer of leaf-litter and humus on the floor. Forests are important pedogenic agents. The development of the soil and of the natural vegetation it supports are co-ordinate and interdependent. The moderating influence of forests on the temperature is distinctly notice able. Trees act as pumps tapping the ground water from considerable depths and transfer it as moisture to the air, thereby increasing the relative humidity. Forests affect the ground water-table according to the initial nature of the soil and the topography : in dry soils and on slopes the water-holding capacity increases, but in ground liable to marshy or swampy conditions, forests tend to lower the water table and exercise a draining effect. The influence of’ forests on rainfall has been much debated: while forests do not affect the primary meteorological causes of rainfall, they do have a noticeable effect on the incidence and distribution of local precipitation (as shown by observations in Ootacamund, South India, extending over a period of years). The problem of soil erosion arises from the imprudent use of land and the indiscriminate destruction of forest cover. Planned afforestation has an important role in the rehabilitation of eroded lands. Narrow shelter belts of trees can afford effective protection against wind erosion. The solution of the problem of soil erosion lies in rational land use. Forests perform a unique function of biological interest in affording shelter for wild fauna. They are also of considerable recreational value to man. On purely commercial considerations alone forests may not be as profitable as other uses to which the land can be put, but the steady supply of forest products and the protective benefits of a forest cover are of paramount importance. Such commercial considerations have no real place in the long term policies associated state ownership of forests.